Análisis del nivel de eficiencia de la preparación física en los deportistas de la selección de fútbol de la Universidad Nacional de Loja, año 2023. - González Jiménez, Johanna Cecibel (2024)
The present Curricular Integration Work, was developed with the objective of analyzing the efficiency of the design of the physical preparation of the athletes of the soccer team at the National University of Loja, year 2023, considering that currently in the soccer players every day there is a greater demand within the physical preparation so that in this way they can perform a good sports training and have a greater performance within the game. For the elaboration of the theoretical framework, the bibliographic review and scientific information extracted from different texts and the Internet were used for the respective conceptualization. The methodology applied included the development of a descriptive non-experimental study, making use of scientific, empirical, analytical-synthetic methods and observation, which was carried out to evaluate the documentation of the physical preparation design provided by the technician in charge. The results showed that the physical preparation planning of the UNL soccer team players is deficient since they do not have complete and organized training plans. Key words: physical preparation, soccer, sports training.